Opportunity or Risk? Appraisal and Affect Mediate the Effect of Task Framing on Working Memory Performance in University Students - Chen, Luxi; Qu, Li (Frontiers in Psychology, 2021)
Working memory (WM) is crucial for reasoning, learning, decision-making and academic achievement. Based on the theories of challenge and threat appraisals, this study experimentally examined whether university students’ WM performance would be optimized by opportunity-focused task instruction or debilitated by risk-focused instruction, by altering cognitive appraisals and affective responses. Ninety-seven university students were randomly assigned to one of the three framing conditions (Opportunity, Risk, vs. Null), and received instructions that differed in consequences (gain for top performers, loss for poor performers, vs. null), goals (approach, avoidance, vs. neutral), and feedback on personal competence (adequate, inadequate, vs. null). WM performance, challenge and threat appraisals, and positive and negative affect were measured before and after task framing. Results showed that students improved WM performance after receiving opportunity-focused task instruction, whilst their counterparts who received risk-focused task instruction increased threat appraisal and decreased positive affect compared to baselines. Mediation analysis revealed that task framing influenced students’ WM performance by altering threat appraisal and positive affect. In addition, task framing exerted larger effects on female students than on male students. The crucial roles of cognitive appraisals and affective responses in WM performance, and implications for educational instructions are discussed.